Legal pharmacy and ethics - Tubon, Nelson T. (Manila, Philippines : Infopage Education Services, Inc., 2020)
This book can be a basic textbook and reference for pharmacy students, educators and practicing pharmacist who will be exposed to varied areas of practice.
1. Regulating standards and controls of the pharmacy profession in the Philippines -- 2. Standards of the practice of pharmacy and pharmaceutical education -- 3. Standards for food, drugs, cosmetics and devices -- 4. Control in the use of dangerous drugs and counterfeit drugs -- 5. Accessibility of drugs -- Appendices -- Glossary -- Bibliography.
Includes bibliographical references.
Keywords: LEGISLATION, PHARMACY; PHARMACY - LAW AND LEGISLATION